Incidence of post-thrombotic syndrome and its association with various risk factors in a cohort of Spanish patients after one year of follow-up following acute deep venous thrombosis - Gabriel, Francisco; Labiós, Manuel; Portolés, Olga; Guillén, Marisa; Corella, Dolores; Francés, Francesc; Martínez, Marcial; Gil, Joaquin; Saiz, Carmen (Thrombosis and Haemostasis, 2004)
Post-thrombotic syndrome (PTS) is a frequent complication of deep venous thrombosis (DVT). However, neither the incidence nor the moment of PTS appearance are known. The main reason are the criteria used to define PTS, the characteristics of the patients, the study design and the time of follow-up. Our aims were to estimate the early incidence of PTS and its associated factors in a cohort of carefully defined DVT patients. 135 patients with a previous episode of acute idiopathic, phlebographically confirmed DVT, in the lower limbs, were followed up over 12 months. Phlebography was then repeated to determine the appearance of PTS. In addition, we used a validated clinical scale in order to assess the correlation between the clinical and phlebographical diagnosis of the PTS. This scale was applied at 6 and 12 months. The incidence of phlebographically confirmed PTS within the first year was 56.3% for the isolated PTS and 5.9% for PTS plus recurrent DVT, regardless of age, sex, platelet count, INR, or anticoagulation. None of these patients could be diagnosed as having PTS using the clinical validated scale. However, those patients with phlebographically diagnosed PTS had a higher clinical score than those without (P = 0.012). The only factor related to a higher risk of developing a PTS was the localization of the DVT, subjects with both proximal and distal DVT having the highest incidence (P = 0.001). In conclusion, although patients had appropriate anticoagulation, early incidence of PTS was very high, thus making it necessary to develop better diagnostic methods in order to evaluate the PTS impact.
Keywords: Post-thrombotic syndrome; recurrent venous thrombosis; Eco-Doppler; phlebography; validated clinical scale